Effectiveness of use of online games kahoot! chemical to improve student learning motivation - Leony Sanga Lamsari Purba; Elferida Sormin; Nelius Harefa; Sumiyati Sumiyati (Pascasarjana Universitas Negeri Medan, 2019)
Qualitative descriptive study quasi-experimental method is intended to determine the effectiveness of using online games Kahoot! to increase student motivation to learn chemistry. The population in this study were all students of class X private secondary schools (SMAs) Pusaka 1 Jakarta. The sample was selected by random sampling technique, the entire class X MIA 1 with the number of 40 students. The results showed the use of online games Kahoot! effective to increase student motivation to learn chemistry. Increased motivation to learn by using the test gain with the gain of 0.73 with the interpretation of the increase motivation to learn the high category. All the indicators of motivation to learn, which has the intention to succeed in learning, to feel the need to be learned, have ideals, appreciate the lessons and study give a percentage increase motivation to learn different. The most significant increase occurred in the indicator have a desire to succeed in learning, with high gain values, namely 0.82. The lowest increase occurred in the indicator value learning, the value of the gain medium, which is 0.70. Thus, the use of online games Kahoot! help improve students' motivation to learn chemistry when applied to learning. Kahoot! use of online games! help improve students' motivation to learn chemistry when applied to learning. Kahoot! use of online games! help improve students' motivation to learn chemistry when applied to learning.Keywords:Chemical; industry 4.0; kahoot!; learning; media; motivation